Perforated Meckel's diverticulum in omphalocele in a newborn: A case report of an uncommon presentation from northern Tanzania. (August 2021) - Lodhia, Jay; Shadrack, Mathayo; Msuya, David; Msuya, Levina; Philemon, Rune
Abstract: Introduction and importance: The concurrent existence of Omphalocele and Meckel's diverticulum is not unheard of but is relatively uncommon. A few cases of their coexistence have been reported. Due to the uncommon dual presentation, it is easy to delay or even miss the diagnosis, delaying management. Meckel's diverticulum should be considered if there is a bowel opening on an omphalocele. Case presentation: Herein we present a newborn male baby who was referred to us presenting with an omphalocele that was leaking faeces. The baby also had a cleft lip and palate. He was born at term to a 30-year-old mother whose pregnancy was otherwise normal. The fistulated omphalocele was surgically repaired, and the child continued to do well. Clinical discussion: Omphalocele and Meckel's diverticulum are both relatively rare congenital malformations that are uncommonly present together. Other congenital malformations can be associated; hence thorough investigations should be carried out when resources are available. The search for associated malformation should not delay the management of the pathology as it can have serious consequences on the health and outcome of the child. Conclusion: Fistulation of Meckel's diverticulum on an Omphalocele is rare. Treatment involves surgical resection and repair. Though other co-morbidities should be investigated, investigation for cause and other co-morbidities should not delay surgery. Highlights: Omphalocele and Meckel's diverticulum rarely occur concurrently. Surgery is the mainstay of management of both malformations. Co-morbidities need to be addressed but not necessarily in the same sitting.